2003
DOI: 10.1051/0004-6361:20030946
|View full text |Cite
|
Sign up to set email alerts
|

High resolution spectroscopy of circumstellar material around A stars

Abstract: Abstract.We have analysed a time series of high resolution spectra (R = 217 000) of the Ca K line of 9 stars which are candidates for the presence of circumstellar material from our previous studies. We have searched for variable narrow absorption components similar to those extensively studied in the case of β Pictoris. Our data show long-term variations in the spectra of HR 2550 and HR 3685 which can be attributed to the dynamics of circumstellar gas. About one third of the sample stars show variable line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
6
12
1
Order By: Relevance
“…Secondly, δ Vel is known to have a moderate thermal infrared excess (e.g., Aumann 1985;Su et al 2006), and Spitzer observations revealed a spectacular bow shock caused by the motion of δ Vel in a dense interstellar cloud (Gáspár et al 2008). The presence of interstellar material was also reported by Hempel & Schmitt (2003), who observed two red-shifted absorbing components in absorption in the Ca II K line of probably interstellar origin. In Paper I of the present series, Kervella et al (2009) confirmed that the infrared excess is essentially emitted by the bow shock, and not warm circumstellar material located close to the stars.…”
Section: Introductionsupporting
confidence: 76%
“…Secondly, δ Vel is known to have a moderate thermal infrared excess (e.g., Aumann 1985;Su et al 2006), and Spitzer observations revealed a spectacular bow shock caused by the motion of δ Vel in a dense interstellar cloud (Gáspár et al 2008). The presence of interstellar material was also reported by Hempel & Schmitt (2003), who observed two red-shifted absorbing components in absorption in the Ca II K line of probably interstellar origin. In Paper I of the present series, Kervella et al (2009) confirmed that the infrared excess is essentially emitted by the bow shock, and not warm circumstellar material located close to the stars.…”
Section: Introductionsupporting
confidence: 76%
“…This A1 III star, located at a distance of 35 pc, is often referred to as being "Vega-like," but Redfield et al [64] have failed to detect a significant mid-IR excess that is normally associated with emission from a surrounding dusty debris disk. Previous observations of this star by Hempel and Schmitt [65] have shown a variation in both the EW of the CaII K-line and its absorption velocity recorded over a sixyear time period. In addition, very high spectral resolution observations of the CaII K-line by Redfield et al [64] revealed Figure 3: The circumstellar CaII K-line absorption spectra of HD 58647 recorded on 4 nights in March 2013.…”
Section: Hd 9672mentioning
confidence: 65%
“…we have detected nightly variations in the Ca  K line of β Pic (Hempel & Schmitt 2003). Brandeker et al (2004) analyzed the spatial structure of the β Pic gas disk in a distance range from the star from 13 AU out to 323 AU and found 88 spatially resolved emission lines in their UVES spectra.…”
Section: A Boundary Layer?mentioning
confidence: 98%